H3K9 acetylation modification and TLR9 immune regulation mechanism in patients after anti-HBV treatment - Zhu, Haipeng; Wang, Ke; Du, Wei; Cao, Huanhuan; Zhong, Qingyang; Yin, Sichun; Zhong, Jianbo; Li, Fawu (Medicine (Baltimore), 2022)
To improve the curative effect of anti-hepatitis B virus (HBV) drugs, methods such as thymosin and entecavir combination have become a focus of clinical investigation. The aim of this retrospective experimental study was to explore the potential mechanism of action of thymosin a1 (Ta1) combined with entecavir in the treatment of HBV infection. A total of 28 patients with chronic hepatitis B, 29 patients treated with thymosin a1 and entecavir combination, and 15 healthy individuals were enrolled in this study. RT-qPCR was conducted to evaluate the mRNA levels of TLR9 in peripheral blood mononuclear cells (PBMCs). The serum level of TLR9 protein was analyzed by ELISA. The binding of TLR9 gene to the protein H3K9Ac in PBMCs was assessed by chromatin immunoprecipitation, and serum inflammatory factors were detected by Luminex technology. The expression levels of TLR9 mRNA and serum TLR9 protein in patients with HBV infection were significantly lower than those in subjects in the control group before treatment but increased after treatment with the Ta1 and entecavir combination. Moreover, the acetylation protein H3K9Ac was significantly bound to the promoter region of the TLR9 gene in patients with HBV infection treated with the Ta1 and entecavir combination compared to that in patients with HBV infection without treatment. Furthermore, the expression levels of interleukin 6 (IL-6), interleukin 12 (IL-12), interferon gamma, and necrosis factor alpha in patients with HBV infection after the combination treatment were slightly decreased compared to those in patients with HBV infection without treatment. In conclusion, the histone acetylation modification of TLR9 was significantly improved in patients with HBV infection after treatment with the Ta1 and entecavir combination, which elevated the expression of TLR9 at the mRNA and protein levels and further regulated the expression of IL-6, IL-12, and other cytokines.